Effects of Physical Activity on Executive Function of Children with ADHD - Hart, Jeffery L.; Phillips, David (Journal of the American Academy of Special Education Professionals, 2020)
Children with ADHD are often described as experiencing deficits in executive function. Two key areas of concern are inhibition, the ability to refrain from a dominant response when needed, and updating, the ability to revise or update incoming information. The purpose of this manuscript is to combine disparate lines of research to help establish a positive link between moderate to vigorous physical activity, executive function, and ADHD. Neuroscience research suggests moderate to vigorous physical activity may increase allocation of attentional resources as evidenced by increases in P3 amplitude and reduce P3 latency in children with ADHD. Intervention studies employing moderate to vigorous physical activity have shown improvements in executive function for children with ADHD. Optimal stimulation and dopamine regulation are suggested as theoretical perspectives for the effects of exercise. Key variables and implications for teachers suggest moderate to vigorous physical activity may provide a quick and effective means of improving executive functioning of children with ADHD in the classroom.